A Review of High School Students' Interest in Swimming: Descriptive Study of 10th Grade Students in Pariaman - M. Kevin Nur Syamsu; Pringgo Mardesia; Tjung Hauw Sin; Naluri Denay (STKIP Pasundan, 2026)
This study aimed to determine the interest of tenth-grade students at SMA Negeri 1 Pariaman in swimming sports. This research used a descriptive quantitative method with a survey approach. The population consisted of 341 tenth-grade students, while the sample included 51 students selected through random sampling. The research instrument was a questionnaire consisting of 37 statement items covering internal and external factors affecting students’ interest in swimming. Data were analyzed using descriptive statistical techniques in the form of percentages. The results showed that students’ interest in swimming was generally in the moderate category. Internal factors were categorized as high, while external factors were categorized as moderate. These findings indicate that students already have good internal motivation toward swimming, although external support such as facilities, family, and environment still needs improvement. Therefore, support from schools and families is needed to increase students’ interest in swimming activities.